A STATISTICAL APPROACH TO IMPROVE SPLITTING TENSILE STRENGTH AND WORKABILITY IN PALMYRA FIBER CONCRETE - Ogunleye , Abiola T; Adediran, Temitope R (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
In this paper, optimization of splitting tensile strength and workability of palmyra fibre reinforced concrete was conducted using mixture design of experiment. Thus, twenty-one (21) concrete mixes which constitute single (main) effect, binary interaction and axial blends design points of second order simplex design was generated from iteration of palmyra fibre content varied at 0.5-3% by weight of cement in concrete. The concrete mix proportion was designed for minimum characteristic compressive strength of 20 N/mm2 at 28 days curing period. The workability of the concrete mixes was determined by slump test after which test specimens were produced using 100 ???????? diameter, 200 ???????? high cylindrical moulds for tensile strength and cured for 28 days. Splitting tensile strength test of the fibre reinforced concrete was conducted after the curing period. The 2nd order simplex polynomial model was fit to the experimental data. Analysis of variance (ANOVA) was used to study the influence of model parameters and their interactions using Minitab 17. Furthermore, the parameters were optimized by maximizing splitting tensile strength and slump values using desirability approach. The optimum settings of parameters are the mixture pseudo components for maximizing the tensile strength and slump test values. The slump has desirability of 0.669138 and the split tensile strength has desirability of 0.459730. The overall desirability index for the responses is 0.554638 at tensile strength of 3.2382 N/mm2 and slump of 19.32 mm.